2017
DOI: 10.1002/mame.201700042
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of Polymeric Biomaterials Containing Carbonate Groups: An Overview

Abstract: The modification of biomaterials using nanoadditives can lead to the development of novel materials for a wide variety of biomedical applications such as drug administration systems, tissue engineering, bioresistance coatings, and biomedical instruments. Moreover, a further improvement of mechanical and thermal properties of aforementioned biomaterials while maintaining their dimensional stability is a goal of major scientific researches. Aliphatic polycarbonates (APCs) containing carbonate groups such as poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 165 publications
(481 reference statements)
0
6
0
Order By: Relevance
“…It suggested that nano-additives, particularly aliphatic polycarbonates (APCs), could be used to modify the scaffolds to enhance biocompatibility and control degradation when the scaffolds were embedded in the tissues. 22 The commonlyused biocompatible materials for tissue engineering include chitosan and its composites, poly(3-hydroxybutyrate)/nanohydroxyapatite (PHB/nHA), 23 poly(ɛ-caprolactone) (PCL) and its composites, poly(L-lactic acid) (PLLA) and its composites, poly(D,L-lactic acid-co-glycolic acid), (PLGA) and its derivatives, regenerated silk fibroin and its derivatives, and collagen and its derivatives, as well as composited materials (containing more than one polymer system). 21,24 The detailed polymer list for bio-scaffold designing using electrospinning is summarized in Table I.…”
Section: Characteristics Of Nanofiber Polymers For Tissue Engineeringmentioning
confidence: 99%
“…It suggested that nano-additives, particularly aliphatic polycarbonates (APCs), could be used to modify the scaffolds to enhance biocompatibility and control degradation when the scaffolds were embedded in the tissues. 22 The commonlyused biocompatible materials for tissue engineering include chitosan and its composites, poly(3-hydroxybutyrate)/nanohydroxyapatite (PHB/nHA), 23 poly(ɛ-caprolactone) (PCL) and its composites, poly(L-lactic acid) (PLLA) and its composites, poly(D,L-lactic acid-co-glycolic acid), (PLGA) and its derivatives, regenerated silk fibroin and its derivatives, and collagen and its derivatives, as well as composited materials (containing more than one polymer system). 21,24 The detailed polymer list for bio-scaffold designing using electrospinning is summarized in Table I.…”
Section: Characteristics Of Nanofiber Polymers For Tissue Engineeringmentioning
confidence: 99%
“…In addition, the degradation rate of PCs is slower than that of polyesters. Due to all of these promising advantages, PCs have attracted great interest [ 5 ] concerning their potential application in many areas.…”
Section: Introductionmentioning
confidence: 99%
“…Sawdust together with urea‐formaldehyde resin was used to improve mechanical properties of banana fibers 14 . Carbon nanotubes were made from sawdust and used to create polypropylene‐based nanocomposites with magnetic properties 15 —while of course other options in making polymer‐based nanocomposites exist 16 . Another original use of sawdust was combining it with polysulfone to create membranes for water desalination 17 …”
Section: Introductionmentioning
confidence: 99%